Sustainable Electrocatalytic Oxidant‐Free Syntheses of Thiosulfonates from Thiols. Issue 23 (28th September 2018) - Yang, Zhongzhen; Shi, Yuesen; Zhan, Zhen; Zhang, Hao; Xing, Huimin; Lu, Runxin; Zhang, Yiming; Guan, Mei; Wu, Yong
Abstract: A novel, efficient and eco‐friendly synthetic strategy for the preparation of thiosulfonates by electrochemical oxidation of thiols is presented. This method enabled thiosulfonates formation under catalyst‐ and oxidant‐ free conditions. The electrochemical oxidizing reaction exhibits a good functional group compatibility and broad scope, hence, providing accesses to various disulfides (31 examples) and thiosulfonates (23 examples). The reactions proceeded under simple and mild reaction conditions, and could be scaled up to the gram‐scale. They are also applicable in the late‐stage synthesis of bioactive molecules. Abstract : An efficient and eco‐friendly synthetic strategy for electrochemical oxidation of thiols to thiosulfonates under mild conditions is presented. This method enabled thiosulfonates formation with good functional group compatibility, providing accesses to various disulfides (31 examples) and thiosulfonates (23 examples). The reactions could be scaled up to the gram‐scale and is also applicable in the late‐stage synthesis of bioactive molecules.